Criminological Aspect on Case of Prostitution around Poncol Station Semarang - Wicaksono, Andri Aditya; Saefudin, Yusuf Rizky; Ramadhan, Hafiz; Pangestu, Rico Alfian; Arifin, Ridwan (Law Research Review Quarterly, 2020)
Prostitution is an anti-social sexual deviation because it violates the norms of decency, norms of decency, customary norms and religious norms. This prostitution occurs in society in the form carried out by a group or individual in an organized manner consisting of pimps, the purpose of getting wages or rewards from those who have used their services. there are two parties namely PSK (Commercial Sex Workers) and masher men as customers. In the Criminal Code (KUHP) only regulates pimps, not yet regulating PSK and its customers. This has an impact on the development of prostitution in people's lives. Prostitution is regulated in Article 296 and Article 506. There are various factors behind the occurrence of this prostitution, such as economic factors caused by economic pressures and life burdens, there are also social factors such as the social environment, and family factors due to divorce or family problems. This study aims to find out what factors underlie the phenomenon of a CSW and analyze based on the perspective of criminological law. This research is located at Semarang Poncol Station on Jalan Imam Bonjol Semarang. This research uses an empirical and qualitative juridical approach. The results of the research and discussion show that the author obtained, among others, can be explained through the formulation that we discussed, namely: The characteristics that exist in the perpetrators of street prostitution, the impact on prostitution, technicalities in transactions between customers and prostitutes, and theories justify the existence of deviations in prostitution.